Effects of folic acid on oxidative damage of kidney in lead-exposed rats - Li, Ning; Wen, Liuding; Yu, Zengli; Li, Tiange; Wang, Tianlin; Qiao, Mingwu; Song, Lianjun; Huang, Xianqing (Frontiers in Nutrition, 2022)
Lead (Pb) has many applications in daily life, but in recent years, various problems caused by lead exposure have aroused people's concern. Folic acid is widely found in fruits and has received more attention for its antioxidant function. However, the role of folic acid in lead-induced kidney injury in rats is not clear. This study was designed to investigate the effects of folic acid on oxidative damage in the kidney of rats caused by lead exposure. Forty SPF male SD rats were randomly divided into four groups: control group, lead exposure group, lead+folic acid group and folic acid group. The control group and the folic acid group were given free drinking water, the lead exposure group and the lead+folic acid group were given water containing 0.2% lead acetate; the control group and the lead exposure group were intragastrically administered with 1 ml of normal saline, and the lead+folic acid group and the folic acid group were intragastrically administered with folic acid (0.4 mg/kg). Lead exposure significantly increased the content of lead and MDA, and the activity of related antioxidant enzymes decreased significantly. Meanwhile, the expressions of Nrf2, HO-1, GRP78 and CHOP were significantly increased, but these adverse changes could be improved by folic acid intervention. Therefore, folic acid can repair kidney oxidative damage caused by lead exposure, which may be related to reducing endoplasmic reticulum stress.